Esophago~digestiv·e by-pass operations in unresectable turnors of the esophagus and carolas. - Matteucci, Pablo (Cirugía del Uruguay, 1975)
Esophago-digestive by-pass operaUons are an excellent pallistive method to suppress dysphagia in oncologically unresectabJe turnon of tJ..¡ e Jower esophogus or cardial area. The authors report Orle case oI esophagogastrostomy due to an unresectable adenocarc1noma of the carc!1as, with a 15-month sUI'vival, tlnd a case of esophago-jejuno.stomy due to a carcinoma of <l gastric stump invading cardias, with a 4-month survival. Both cases died without recurrence oí 1heir disphagia, which suggests a positive result as to the quality of fue survival obtained.